2018
DOI: 10.1007/s00415-018-8768-0
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal insulin in Alzheimer’s dementia or mild cognitive impairment: a systematic review

Abstract: Intranasal insulin improved story recall performance of apoe4 (-) patients with AD or MCI. Other cognitive functions were not affected, but there were some positive results in functional status and daily activity. Since IN insulin is a safe intervention, future studies should be conducted with larger doses and after proper selection of patients and insulin types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 63 publications
0
74
0
2
Order By: Relevance
“…Considering the role of insulin in cognition, dysregulation of the brain insulin pathway could be responsible for the cognitive impairments found in AD and T2DM patients. Supporting this hypothesis, pilot clinical trials with intranasal brain insulin delivery have shown improvements in verbal memory and story recall in patients with MCI and AD [48]. Intranasal insulin delivery was used to avoid the systemic side effects of insulin and no major aversive effects were reported [49].…”
Section: A) Alterations In Glucose Metabolismmentioning
confidence: 98%
“…Considering the role of insulin in cognition, dysregulation of the brain insulin pathway could be responsible for the cognitive impairments found in AD and T2DM patients. Supporting this hypothesis, pilot clinical trials with intranasal brain insulin delivery have shown improvements in verbal memory and story recall in patients with MCI and AD [48]. Intranasal insulin delivery was used to avoid the systemic side effects of insulin and no major aversive effects were reported [49].…”
Section: A) Alterations In Glucose Metabolismmentioning
confidence: 98%
“…Increasing insulin in the brains of mice has cognitive and pathological benefits in neurodegenerative models (Chen et al, 2017;Kim et al, 2019;Sanguinetti et al, 2019). Clinical trials of intranasal insulin administration to combat dementia and AD are currently ongoing with mixed results to this point (Avgerinos et al, 2018).…”
Section: Brain Insulin Receptor and Insulin Resistance In Diabetes mentioning
confidence: 99%
“…The mutation of T668A in APP could prevent the phosphorylation of APP in vivo and rescue memory and synaptic plasticity deficits in a familial AD mouse model [144]. Insulin and insulin-like growth factor I (IGF-I) are now under clinical trial for AD [145]. Data from Kim et al proved that both insulin and IGF-I can reduce the phosphorylation of APP at the T668 residue by activating the PI3K/Akt pathway [146].…”
Section: Targeting the Phosphorylation Signaling In App Processing Fomentioning
confidence: 99%